Prognostic impact and change of concomitant mitral regurgitation after surgical or transcatheter aortic valve replacement for aortic stenosis. Issue 6 (June 2016) - Fojt, Richard; Moťovská, Zuzana; Budera, Petr; Malý, Marek; Straka, Zbyněk
Abstract: Background: Significant aortic stenosis (AS) is frequently associated with mitral regurgitation (MR) of varying degrees. We sought to assess the change in MR grade after the aortic valve procedure, to find predictors of MR improvement and finally to determine the prognostic impact of persistent MR. Methods: We retrospectively analyzed a group of 101 AS patients who underwent aortic valve replacement (AVR) or transcatheter aortic valve implantation (TAVI) at our institution between January 2007 and March 2014 and who presented with MR grade 2 or higher on preoperative echocardiogram – 35 patients underwent an isolated AVR, 18 underwent TAVI, and the rest underwent a combined procedure, which included coronary artery bypass grafting. The mean follow-up was 28.5 ± 21 months. Results: MR improved significantly after the procedures (2.4 ± 0.5 vs. 1.9 ± 0.9, p < 0.001) and a decline in the severity of MR was observed regardless of etiology (degenerative/post-rheumatic, functional/ischemic, combined) without significant changes between groups ( p = 0.667). Downgrading of MR severity was associated with improvement in ejection fraction ( p = 0.021) and reduction in the size of cardiac chambers, especially the left atrium (left atrial diameter, p < 0.001). None of the preoperatively evaluated factors (severity of AS, MR etiology, ejection fraction, cardiac chamber dimensions, coronary artery disease, and New York Heart Association functional class) was a significant predictor of MR improvement. Persistence of higher degrees of MR was associated with a more frequent need for cardiovascular hospitalization, while the survival rate 3 years after procedure was not affected ( p = 0.146). Conclusions: In the majority of AS patients, an aortic valve procedure leads to reduction in coexistent MR. A significant decrease in the severity of MR in our study was observed regardless of etiology and preoperative grade of MR. Persistence of higher degrees of MR was associated with increased patient morbidity.